2017
DOI: 10.1155/2017/4174573
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Congenital Anomalies among Surgical Patients at a Tertiary Care Centre over 4 Years

Abstract: Introduction. Congenital anomalies are important causes of childhood death, chronic illness, and disability in many countries. Congenital malformations are rapidly emerging as one of the major worldwide problems. Aim. To study the percentage of various congenital anomalies among the patients admitted in Department of Pediatric Surgery at a tertiary care centre over a period of four years from 2011 to 2015 in our centre. Results. Neural tube defects were found to be the most common anomalies in 24.3% of the chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
0
4
4
Order By: Relevance
“…16 However, unlike other studies, we found hydrocephalus as the most common anomaly, whereas others have reported NTDs as the most common anomaly of the CNS. [16][17][18] Different from Adeleye and Olowookere, 17 who reported most hydrocephalus being related to aqueductal stenosis, most of our cases of hydrocephalus were related to NTDs. Among NTDs, similar to other studies, we found spinal dysraphisms to be more common than encephaloceles.…”
Section: Discussioncontrasting
confidence: 99%
“…16 However, unlike other studies, we found hydrocephalus as the most common anomaly, whereas others have reported NTDs as the most common anomaly of the CNS. [16][17][18] Different from Adeleye and Olowookere, 17 who reported most hydrocephalus being related to aqueductal stenosis, most of our cases of hydrocephalus were related to NTDs. Among NTDs, similar to other studies, we found spinal dysraphisms to be more common than encephaloceles.…”
Section: Discussioncontrasting
confidence: 99%
“…It was found that CMGIT more commonly involved females (54.3%). This is contradictory to other studies where they found more prevalence of congenital anomalies in males 1,5 .…”
Section: Discussioncontrasting
confidence: 99%
“…And shamim et al has reported anorectal malformation as 20% of GIT malformations. In studies from India it has been reported as anorectal malformation as most common GIT anomaly making 20% of CMGIT 1,5,12 . In study by Ochaga et al has shown anorectal malformation as 66% of GIT anomalies 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in congruence with other studies, such as that by Babu et al (45.94% in a 1000 birth cohort) and Agarwal et al (24.3%). 9 The proportion of women with fetal congenital malformations who had previous abortions was 9.27%. Almeida et al have shown that presence of previous abortions is a risk factor for congenital malformations.…”
Section: Discussionmentioning
confidence: 99%